Essential Biomaterials Science - Williams, David (Cambridge: CUP, 2014)
This groundbreaking single-authored textbook equips students with everything they need to know to truly understand the hugely topical field of biomaterials science, including essential background on the clinical necessity of biomaterials, relevant concepts in biology and materials science, comprehensive and up-to-date coverage of all existing clinical and experimental biomaterials, and the fundamental principles of biocompatibility. It features extensive case studies interweaved with theory, from a wide range of clinical disciplines, equipping students with a practical understanding of the phenomena and mechanisms of biomaterials performance; a whole chapter dedicated to the biomaterials industry itself, including guidance on regulations, standards and guidelines, litigation, and ethical issues to prepare students for industry; informative glossaries of key terms, engaging end-of-chapter exercises, and up-to-date lists of recommended reading. Drawing on the author's 40 years' experience in biomaterials, this is an indispensible resource for students studying these lifesaving technological advances.
Index 631-640p.
Keywords: Diagnostic systems; Tissue engineering; Biocompatibility pathways